The chromosome-level reference genome assembly for Dendrobium officinale and its utility of functional genomics research and molecular breeding study - Zhitao Niu; Fei Zhu; Yajuan Fan; Chao Li; Benhou Zhang; Shuying Zhu; Zhenyu Hou; Mengting Wang; Jiapeng Yang; Qingyun Xue; Wei Liu; Xiaoyu Ding (Elsevier, 2021)
Dendrobium officinale, an important medicinal plant of the genus Dendrobium in Orchidaceae family, has been used as traditional Chinese medicine (TCM) for nearly thousands of years. Here, we report the first chromosome-level reference genome of D. officinale, based on PacBio long-reads, Illumina short-reads and Hi-C data. The high-quality assembled genome is 1.23 Gb long, with contig N50 of 1.44 Mb. A total of 93.53% genome sequences were assembled into 19 pseudochromosomes with a super scaffold N50 of 63.07 Mb. Through comparative genomic analysis, we explored the expanded gene families of D. officinale, and also their impact on environmental adaptation and biosynthesis of secondary metabolites. We further performed detailed transcriptional analysis of D. officinale, and identified the candidate genes involved in the biosynthesis of three main active ingredients, including polysaccharides, alkaloids and flavonoids. In addition, the MODIFYING WALL LIGNIN-1 (MWL1) gene, which inferred from Genome-Wide Association Studies (GWAS) based on the resequencing date from D. officinale and five related species and their morphologic features, may contribute to the plant production (yield of stems) of D. officinale. Therefore, the high-quality reference genome reported in this study could benefits functional genomics research and molecular breeding of D. officinale.